High-performance oxygen reduction electrocatalysts derived from uniform cobalt–adenine assemblies. (October 2015) - Shen, Mengxia; Zheng, Li-Rong; He, Wenhui; Ruan, Changping; Jiang, Chunhuan; Ai, Kelong; Lu, Lehui
Abstract: Enhancing the catalytic activity of non-precious metal catalysts (NPMCs) for oxygen reduction reaction (ORR) requires determination of active centers and a better understanding of the structure–activity relationship. However, key technical challenges in controlling the structural uniformity of NPMCs and maximizing the number of exposed active sites make this goal hard to achieve. Here, inspired by the facile self-assembly strategy for DNA metallization, we have fabricated Co–adenine nanocomposite spheres (Co–A NSs) with uniform structures and well-recognized Co–N4 configuration. Direct pyrolysis of Co–A NSs leads to the formation of monodisperse rambutan-like Co–N/C composites with high porosity and degree of graphitization, as well as homogeneous and high-density Co–N active sites, which endow them with excellent ORR catalytic activity in both base and acid conditions. With Co–N/C as the cathode catalyst, the assembled alkaline direct methanol fuel cell (ADMFC) generates extremely high open-circuit voltage (0.80 V) and unprecedentedly high maximum output power density (40.1 mW cm −2 ), which is successfully utilized to illuminate a light-emitting diode (LED) lantern. Moreover, the easily controlled structure of Co–N/C catalysts enables us to further reveal their structure–activity relationship, which may provide guidance for future design of advanced electrocatalysts. Graphical abstract: Highlights: DNA metallization shed light on the coordination-driven self-assembly strategy. Co–N/C maintained the structural uniformity and high-density Co–N active sites. The alkaline direct methanol fuel cell generated high maximum power density. The Co–N species in Co–N/C and the structure–activity correlation were demonstrated.